2016
DOI: 10.1016/j.drugalcdep.2016.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain, craving, and illicit opioid use among patients receiving opioid agonist therapy

Abstract: Aims In a sample of patients receiving opioid agonist therapy, we evaluated whether having chronic pain was associated with a) craving for opioids and b) illicit opioid use. Methods In a cross-sectional study of adults on buprenorphine or methadone maintenance recruited from an urban medical center, we examined any craving for opioids (primary dependent variable) in the past week and recent illicit opioid use (secondary dependent variable). Illicit opioid use was defined as a positive urine drug test (UDT) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…Being dispensed a benzodiazepine or z-hypnotic was particularly associated with being dispensed non-OAT opioids, and gabapentinoids, as well as methadone rather than buprenorphine as the type of OAT opioid. Chronic nonmalignant pain like pain in muscles and skeleton is highly prevalent in the OAT population using methadone as an OAT opioid and affects up to 68% in some studies [28][29][30][31]. Having chronic non-malignant pain on OAT is strongly associated with using benzodiazepines [26,27], and the presence of psychiatric comorbidities such as anxiety and depression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Being dispensed a benzodiazepine or z-hypnotic was particularly associated with being dispensed non-OAT opioids, and gabapentinoids, as well as methadone rather than buprenorphine as the type of OAT opioid. Chronic nonmalignant pain like pain in muscles and skeleton is highly prevalent in the OAT population using methadone as an OAT opioid and affects up to 68% in some studies [28][29][30][31]. Having chronic non-malignant pain on OAT is strongly associated with using benzodiazepines [26,27], and the presence of psychiatric comorbidities such as anxiety and depression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain is highly prevalent in treatment-seeking, opioid-dependent populations with between 36% and 68% affected (Barry et al, 2013;Tsui et al, 2016). Thus, chronic pain is an important clinical condition to be considered by addiction specialists.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between pain and substance dependence is a complex and important clinical issue 1 . Studies have demonstrated that pain is very common among patients with various types of drug dependence disorders 2 4 , and chronic pain is associated with the development and relapse of opioid addiction, and craving for opioids 5 , 6 . Further, studies also found that chemically dependent patients with clinically significant pain (CSP) are more likely to self-medicate with other illicit drugs, alcohol, and non-prescribed drugs 2 , 7 – 10 .…”
Section: Introductionmentioning
confidence: 99%